Síndrome del cuidador y funcionalidad familiar en las personas con dispacidad, Loja 2016. - Quinche Suquilanda, Álvaro Manuel (2017)
The syndrome of the caregiver in severe and very serious disability represents a very prevalent problem, having serious repercussions on the patient and caregiver´s life. It is due to the inexistence of studies on this subject and its complications why I have engaged in this research, the objective of the study was to establish the relationship between the caregiver's syndrome and family functionality in the population under study, as well as to perform the characterization of the caregiver, of the syndrome and of the family functionality, as well as demographic and socio-economic factors, the methodology used was descriptive, relational, with a cross-sectional design of caregivers of persons with severe and very serious disabilities in the Province of Loja 2016. In a sample of 397 caregivers, the information was obtained after the application of a personal data sheet to collect information on socio-demographic aspects of the patient and the caregiver, as well as scales to determine family functionality, such as Family Apgar and Caregiver Syndrome with the Zarit test. The results show a statistical association between these variables, with a chi chart of 4.77 and a P value of 0.029 indicating a significant statistical association between these variables. The correlations show that the greater the state of dysfunction of people with disabilities the harder the work overload of caregivers. These results show the reality of the daily life of the caregivers, realities not visualized by the medical teams, nor valued as people with a high degree of physical and psychological vulnerability. In conclusion, with the obtaining of the data, the necessary parameters are being provided to guide interventions aimed at improving the quality of life of caregivers by government entities. Keywords: overload, dysfunction, syndrome, Zarit